The mechanism of magnetic flux rope rotation during solar eruption - Zhou, Zhenjun; Jiang, Chaowei; Yu, Xiaoyu; Wang, Yuming; Hao, Yongqiang; Cui, Jun (Frontiers in Physics, 2023)
Solar eruptions often shows rotation of filaments, which is manifestation of the rotation of erupting magnetic flux rope (MFR). Such a rotation of MFR can be induced by either the torque exerted by an background shear-field component (which is an external cause) or the relaxation of magnetic twist of the MFR (an internal cause). For a given chirality of the erupting field, both of the external and internal drivers cause the same rotation direction. Therefore, it remains elusive from direct observations which mechanism yields the dominant contribution to the rotation. In this paper, we exploit a full MHD simulation of solar eruption by tether-cutting magnetic reconnection to study the mechanism of MFR rotation. In the simulation, the MFR’s height–rotation profile suggests that, the force by the external shear-field component is a dominant contributor to the rotation. Furthermore, the torque analysis confirms that it is also the only factor in driving the counterclockwise rotation. On the contrary, the Lorentz torque inside the MFR makes a negative effect to this counterclockwise rotation.